Panton-Valentine Leucocidin (PVL) as a Potential Indicator for Prevalence, Duration, and Severity of Staphylococcus aureus Osteomyelitis - Jiang, Bei; Wang, Yinan; Feng, Zihan; Xu, Lei; Tan, Li; Zhao, Shuang; Gong, Yali; Zhang, Cheng; Luo, Xiaoqiang; Li, Shu; Rao, Xiancai; Peng, Yizhi; et al. (Frontiers in Microbiology, 2017)
Staphylococcus aureus is the most common cause of the difficult-to-treat osteomyelitis (OM). To better diagnose and manage S. aureus OM, especially for severe and long duration cases, indicators for risk prediction and severity evaluation are needed. Here, 139 clinical S. aureus isolates from orthopedic infection were divided into OM group (60 isolates from 60 OM patients) and non-OM group (79 isolates from 79 non-OM patients). Molecular types, antimicrobial susceptibility, and virulence factor profiles were evaluated and compared between the two groups to identify potential indicators associated with the incidence of S. aureus OM. Clinical manifestations and laboratory data were analyzed to identify indicators affecting OM duration and severity. We found that some sequence types (STs) were specific to OM infection. The pvl, bbp, and ebps genes were associated with S. aureus OM incidence. The pvl, bbp, and sei genes were associated with relatively longer OM duration. PVL-positive S. aureus OM presented more serious inflammatory responses. Our results emphasize the significance of PVL in affecting the incidence, duration, and severity of S. aureus OM. Diagnosing and monitoring PVL-related S. aureus OM may help direct better prognosis and treatment of these patients.